Polymorphisms in Toll-Like Receptor 10 and Tuberculosis Susceptibility: Evidence from Three Independent Series - Wang, Yu; Zhang, Miao-Miao; Huang, Wei-Wei; Wu, Shou-Quan; Wang, Ming-Gui; Tang, Xiao-Yan; Sandford, Andrew J.; He, Jian-Qing (Frontiers in Immunology, 2018)
Background: The toll-like receptor 2 (TLR2) mediated immune response is critical for host defense against Mycobacterium tuberculosis. There is evidence that TLR10, a TLR2 signaling modulator, may be involved in progression of tuberculosis (TB). Methods: Using a self-validating case–control design, we tested for an association between seven TLR10 polymorphisms and susceptibility to TB in three independent series with two distinct populations. Single nucleotide polymorphism (SNP) genotypes were determined by the SNPscanTM method. Three genetic models (additive, dominant, and recessive) as well as multiple-SNP score analyses were used to evaluate the risk of TB associated with the TLR10 SNPs. Results: By comparing TB patients with healthy controls, we observed two SNPs (rs11466617 and rs4129009) that were associated with decreased risk of TB in the Tibetan population, but did not in the Chinese Han population. Further analysis demonstrated that the rs11466617 CC genotype served as a protective factor against the progression of latent TB infection (LTBI) to active TB under the recessive model. None of the SNPs were significantly different in comparisons of TB uninfected people with LTBI individuals. Additionally, when the underlying four TB-associated loci were considered together in a multiple-SNP score analysis, we observed an allele dose-dependent decrease in TB risk in Tibetans. Conclusion: Variants of TLR10 may show an ethnic specificity on susceptibility to TB in Tibetan individuals. rs11466617 affected the susceptibility to progress from LTBI to active TB disease, but was not associated with the establishment of latent TB infection after Mycobacterium tuberculosis exposure. More studies are needed to verify this genetic epidemiological result and unravel the role of TLR10 SNPs in the pathogenesis of TB.